Broadband and Wide Field-of-View Refractive and Meta-Optics Hybrid Imaging System for Mid-Wave Infrared - Bo Liu; Yunqiang Zhang; Zhu Li; Bingyan Wei; Xuetao Gan; Xin Xie (Nanomaterials)
We propose a wide field-of-view (FOV) refractive and meta-optics hybrid imaging system designed for the mid-wave infrared spectrum (3–5 μm) to address the challenge of high-quality imaging in wide FOV applications. The system consists of only three refractive lenses and two metasurfaces (one functioning as a circular polarizer and the other as a phase element), with a total length of 29 mm. Through a detailed analysis of modulation transfer function curves and spot diagrams, the system achieves 178° FOV while maintaining exceptional imaging performance across a temperature range of −40 °C to 60 °C. The system demonstrates the potential for extending applications to other wavelengths and scenarios, thereby contributing to the advancement of high-performance compact optical systems.